KEMAMPUAN PEMECAHAN MASALAH SISWA PADA POKOK BAHASAN FUNGSI DI KELAS VIII MADRASAH TSANAWIYAH AL-JUNAIDIYAH KAMPUNG LAMO KABUPATEN MANDAILING NATAL - Sari, Nila; Rangkuti, Ahmad Nizar (IAIN PADANGSIDIMPUAN, 2017)
The background of this research problem is the lack of students' ability to associate the concepts they learn with the problems that exist in their environment. In addition to the lack of maximum problem solving abilities of students who, if seen from the causal elements, one of them is the inappropriate learning method applied by the teacher. The problem discussed in this study is about students' problem solving abilities in the function subject in class VIII Al-Junaidiyah Mandailing Natal District. How is the problem solving ability of students in the function subject in class VIII Al-Junaidiyah Mandailing Natal District ?. Problem solving ability is one of the mathematical abilities that can facilitate students in solving problems in mathematics. This study aims to find out how students' problem solving abilities when faced with math problems students VIII Al-Junaidiyah Mandailing Natal District.This research is a qualitative research with descriptive approach method. The research subjects were class VIII Al-Junaidiyah Mandailing Natal District as many as 25 students. To obtain this research data using interview instruments and tests. Data analysis used is tabulation with the application of descriptive data.Based on the results of the study it can be concluded that the problem solving abilities of students on the subject of functions in expressing functions in arrow diagrams are 34.11%, problem solving abilities in expressing functions in cartesius diagrams21.96%, and problem solving abilities in expressing functions in sequential pairs 16.36%, then the problem solving ability in expressing a notation of a function consisting of 2 items, namely number 4 is 16.82% and question number 5 is 10.75%. The conclusions found in this study are the lack of student understanding in the concepts of function, which causes a low ability to solve the problem of class VIII students of Al-Junaidiyah, Mandailing Natal District.